In vitro effects of nonylphenol on motility, mitochondrial, acrosomal and chromatin integrity of ram and boar spermatozoa. (3rd October 2014) - Uguz, C.; Varisli, O.; Agca, C.; Evans, T.; Agca, Y.
Summary The objective of this study was to determine the effects of nonylphenol (NP) on viability of ram and boar sperm in vitro. Ram or boar spermatozoa were exposed to 1, 10, 100, 250 and 500 μg NP ml−1 for 1, 2, 3 or 4 h. Computer‐assisted sperm motility analysis (CASA) system was used to evaluate sperm motility characteristics. Flow cytometry was used to determine mitochondrial membrane potential (MMP) and chromatin integrity, while epifluorescent microscopy was used to determine sperm acrosomal status. Exposure of both species spermatozoa to 250 and 500 μg NP ml−1 was detrimental to progressive motility (P < 0.05), and its adverse effect was significant at lower (100 μg NP ml−1) concentration (P < 0.05). The percentages of ram and boar spermatozoa with high MMP declined drastically after exposures to ≥250 μg ml−1 NP (P < 0.05). Unlike chromatin integrity, which did not appear to be altered by NP exposure, there were dose‐dependent NP effects (P < 0.05) on acrosomal integrity of both species at as low as 1 μg ml−1 NP for boar spermatozoa and 10 μg ml−1 NP for ram spermatozoa. These data show adverse effects of NP on ram and boar spermatozoa and thus its potential harmful effects on male reproduction as NP is found in fruits, vegetables, human milk, fish and livestock products.